Convictions religieuses et adoption ou non-adoption d'une conception sécularisée de la science. Enquête réalisée auprès d'élèves de terminale en Belgique francophone - Wolfs, José-Luis (Zeitschrift für Religionskunde, 2016)
Much research has shown a total or partial rejection in various countries of the theory of evolution by pupils, on the grounds of their religious beliefs. The research presented in this article aims to determine, more globally, to what extent pupils completing secondary education in French-speaking Belgium have or have not acquired a secularised conception of science. Two factors capable of influencing the adoption of a secularised or non-secularised conception of science by pupils are examined more closely: (1) the pupils' personal religious convictions and (for believers) their relation to “Scripture” (2) whether or not they have followed a predominantly scientific curriculum. On the basis of the results of this study, some directions for pedagogical and didactic reflection are discussed.